Implant-Supported Removable Partial Denture Improves the Quality of Life of Patients with Extreme Tooth Loss - Campos,Camila Heitor (2015)
Abstract: This study aimed to evaluate oral health-related quality of life (OHRQoL) in partially dentate subjects, presenting extreme tooth loss in posterior region with missing post-canines, comparing the use of conventional removable partial dentures (RPDs) and implant-supported RPDs. OHRQoL was measured using the Brazilian version of the Oral Health Impact Profile. Twelve subjects presenting maxillary total and mandibular Kennedy Class I edentulism (mean age 62.6±7.8 years) first received complete maxillary dentures and conventional mandibular free-end RPDs. After two months, the subjects had their OHRQoL assessed. Osseointegrated implants were inserted bilaterally in the mandibular first molar regions, and after four months ball abutments were placed to support the free-end RPD. Two months later, the patients had their OHRQoL reassessed. Wilcoxon signed-rank test was used to evaluate differences in OHRQoL (α=0.05). Results showed improvement in all OHIP-49 domains (p<0.05) after associating implants to the RPD. The mandibular implant-supported free-end RPD significantly improved OHRQoL.